Native plant turnover and limited exotic spread explain swamp biotic differentiation with urbanization. Issue 1 (12th December 2020) - Paquin, Léo Janne; Bourgeois, Bérenger; Pellerin, Stéphanie; Alard, Didier; Poulin, Monique
Abstract: Questions: Does urbanization promote biotic differentiation or homogenization of swamp plant communities? What is the contribution of natives and exotics to swamp response to urbanization? Location: Quebec City, Canada. Methods: Plant communities of 34 swamps located in low, moderately or highly urbanized landscapes were sampled, and species classified into three exclusive groups: native wetland, native upland and exotic plants. Urbanization's influence on the richness of each plant group was assessed using mixed models. Between‐site compositional similarities were calculated to identify variations in beta diversity with urbanization level using tests for homogeneity in multivariate dispersion. Beta diversity was further partitioned into species replacement and richness difference for each plant group. Finally, the relationships of ten environmental variables representing soil water saturation and microtopography with plant assemblages were determined by redundancy analysis. Results: Although the richness of exotics increased with urbanization intensity, revealing increasing propagule pressure, it remained six to 27 times lower compared to the richness of natives, which remained stable with urbanization. On the other hand, beta diversity increased with urbanization, with higher dissimilarities in species composition between highly urbanized swamps than between low‐urbanized ones. This pattern resulted from high species replacement among natives, while richness difference mainly contributed to exotic beta diversity. Changes in plant assemblages were mostly associated with bryophyte cover and soil drainage and red mottle size, suggesting that hydrological conditions likely acted as a strong driver of swamp plant community response to urbanization. Conclusions: Swamp plant communities experienced biotic differentiation with increasing urbanization. This differentiation pattern likely was linked to the unpredictable effect of urbanization on hydrological regimes, which promoted high native turnover while limiting exotic spread. Long‐term monitoring is recommended to ensure that exotics do not outcompete natives through time. Designing sustainable cities requires a greater understanding of the multifaceted effect of urbanization on biodiversity. Abstract : Disentangling the multifaceted effect of urbanization on biodiversity is required for designing sustainable cities. Although urbanization often induces biotic homogenization, we revealed that increasing landscape urbanization level is associated with biotic differentiation of swamp plant communities. The unpredictable effect of urbanization on hydrological regimes indeed promoted high native species turnover while limiting exotic spread.